2010
DOI: 10.1111/j.1750-3841.2009.01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation and Postthermal Treatment Growth during Storage of Multiple Salmonella Serotypes in Ground Beef as Affected by Sodium Lactate and Oregano Oil

Abstract: We assessed the heat resistance of Salmonella in raw ground beef in both the absence and presence of sodium lactate, oregano oil, and in combinations of these 2 GRAS-listed ingredients, and determined their bactericidal or bacteriostatic activities during postthermal treatment storage at 15 degrees C. A cocktail of 8 serotypes of Salmonella spp. was inoculated into ground beef supplemented with sodium lactate (NaL) (1.5% and 3%) and/or oregano oil (0.5% and 1%) to obtain approximately 8 log CFU/g. The ground b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
(34 reference statements)
1
21
0
Order By: Relevance
“…Due to quality and sensorial reasons, it is really important to find an optimal time and temperature combination for food heating process. Addition of natural food-compatible additives could decrease optimal time and temperature combinations (Juneja, Hwang, & Friedman, 2010;Juneja, Thippareddi, & Friedman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Due to quality and sensorial reasons, it is really important to find an optimal time and temperature combination for food heating process. Addition of natural food-compatible additives could decrease optimal time and temperature combinations (Juneja, Hwang, & Friedman, 2010;Juneja, Thippareddi, & Friedman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies in laboratory media have covered antimicrobial effects of a variety of natural antimicrobials, including highphenolic plant extracts, against both antibiotic-susceptible and -resistant pathogens (Juneja, Hwang, & Friedman, 2010;Mild et al, 2011;Ravishankar et al, 2010). Studies were also extended to include incorporation of EO into fruit and vegetable purees to produce antimicrobial functional edible films (Du et al, 2008;Du et al, 2009;Ravishankar, Zhu, Olsen, McHugh, & Friedman, 2009;Rojas-Graü et al, 2006;Zhu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This combination did not affect the sensory attributes [65]. OEO and sodium lactate not only reduces the number of microbes but render them more susceptible to heat treatments [66]. These studies showed that OEO, by itself or in combination can be used in raw and processed meats to control pathogens and extend shelf life during chill storage.…”
Section: Antimicrobial Effects In Packaged Raw Meatmentioning
confidence: 85%